THE CERVICAL CANCER NURSING ASSISTANCE: A REVIEW OF THE LITERATURE (CIPEEX, 2022)
INTRODUCTION: BECAUSE OF THE HIGH PREVALENCE AND MORTALITY RATES OF CERVICAL CANCER (UCC), THE MAIN SCREENING STRATEGY IS THE PAP TEST. IN SPITE OF THE CONSTANT EFFORTS IN THE EDUCATION OF THE POPULATION THE ADHESION OF THE EXAMINATION IS BELOW THE RECOMMENDED ONE. THE NURSE HAS A FUNDAMENTAL ROLE IN THE WHOLE PROCESS OF PREVENTION AND HEALTH PROMOTION OF THIS DISEASE, RETURNING TO AN ASSISTANCE IN AN INTEGRATED AND HUMANIZED WAY IN THE PROCEDURE OF COLLECTING THE CYTOPATHOLOGICAL EXAMINATION. OBJECTIVE: TO IDENTIFY NURSING CARE IN THE PREVENTION OF CCU IN LITERATURE REVIEW. METHOD: INTEGRATIVE LITERATURE REVIEW OF ARTICLES PUBLISHED IN THE VIRTUAL HEALTH LIBRARY (VHL) AND AVAILABLE IN FULL TEXT IN THE DATABASES: LATIN AMERICAN AND CARIBBEAN LITERATURE IN HEALTH SCIENCES (LILACS) AND SCIENTIFIC ELECTRONIC LIBRARY ONLINE (SCIELO) AND NURSING DATABASE (BDENF), IN THE PERIOD BETWEEN 2012-2018, IN THE PORTUGUESE LANGUAGE. FOR THE ANALYSIS OF THE DATA THE RECOMMENDATIONS OF MENDES ET AL. (2008), WHICH PROPOSES SIX STEPS FOR THE ELABORATION OF A GOOD, EFFECTIVE, PRECISE AND RELEVANT INTEGRATIVE REVIEW. RESULTS: WE INCLUDED 14 ARTICLES IN THIS REVIEW. TWO CATEGORIES EMERGED: THE COP X THE DIFFICULTIES OF NURSING TO CARRY OUT THE PREVENTION OF CCU AND THE NURSE'S ROLE IN THE PREVENTION OF CCU. THE LACK OF KNOWLEDGE AMONG THE FEMALE POPULATION DETERMINES THE DIFFICULTIES IN PERFORMING THE COP EXAM. WOMEN FEEL EMBARRASSED ABOUT EXPOSING THEIR GENITAL ORGANS AND HAVING THEM MANIPULATED BY A HEALTH PROFESSIONAL, THUS CAUSING DIFFICULTIES FOR THE PATIENT, BECAUSE THE PATIENT CAN NOT RELAX AND THEN HAVE A MORE PAINFUL EXAMINATION THAN THE COMMON ONE. SOME STUDIES HAVE SHOWN THAT THE GYNECOLOGICAL POSITION CAUSES A FEELING OF IMPOTENCE, OR LOSS OF THE BODY'S OWN DOMAIN, CAUSING FEAR DURING THE TEST. THOSE WHO ARE MARRIED FEEL IMMUNE TO SEXUALLY TRANSMITTED DISEASES, AND ANOTHER PARTY SAYS THAT THE TEST IS NOT PERFORMED BECAUSE OF A LACK OF SYMPTOMS OR EMBARRASSMENT TO BE EXPOSED DURING THE COLLECTION. AND THE LACK OF KNOWLEDGE ON THE PART OF THESE WOMEN REGARDING THE NURSE'S ABILITY TO PERFORM THE POP COLLECTION SHOWS THAT THE NURSE PROFESSIONAL IS RESPONSIBLE FOR THE PRACTICE OF COLLECTING THE EXAM, PREFERRING THE MEDICAL PROFESSIONAL. THE NURSING CONSULTATION IS AN ACTION FOR PREVENTION, WHICH CONSISTS OF DATA COLLECTION, PHYSICAL EXAMINATION, CARE PLANNING, NURSING DIAGNOSES AND PRESCRIPTION. IN THIS WAY, THE PROFESSIONAL SHOULD RETURN TO ASSISTANCE FOR TEACHING SELF-CARE. FINAILS CONSIDERATIONS: CERVICAL CANCER IS NOW THE FOURTH CANCER THAT KILLS THE MOST IN BRAZIL THEREFORE, IT IS EXTREMELY IMPORTANT TO PREVENT AND DIAGNOSE EARLY, THIS IS A ROLE FOR NURSES, TO DO IT SUCCESSFULLY SO THAT THERE IS A REDUCTION OF MORTALITY IN THE COUNTRY. TODAY WE CAN OBSERVE THAT THE LACK OF INFORMATION REGARDING THE REFERRED CANCER IS STILL VERY HIGH, SO IT IS ALSO THE ROLE OF NURSING TO ORGANIZE HEALTH EDUCATION IN A WAY THAT CAN RESOLVE TIMELY DOUBTS AND TABOOS THAT PREVENT PREVENTION.
Keywords: Neoplasias do colo uterino. CÃ¢ncer do colo uterino. Prevenção do colo uterino.